Evaluation of Candida tropicalis (NCIM 3321) extracellular phytase having plant growth promoting potential and process development - Puppala, Kumar Raja; Naik, Tejali; Shaik, Alfina; Dastager, Syed; Kumar, V. Ravi; Khire, Jayant; Dharne, Mahesh (Biocatalysis and Agricultural Biotechnology, 2018)
Phytase is known to provide a solution for depletion of phosphorus (P). It helps it by hydrolyzing the insoluble P source in soil which is phytate. In this study, provides insight on yeast Candida tropicalis (NCIM 3321) which produces cell bound and extracellular thermostable phytase. The media components were optimized to enhance the enzyme production and checked for plant growth promoting activity. On optimization the isolate exhibited enhanced cell bound and extracellular phytase activity by four folds (from 236 to 1024 IU DCG⁻¹) and by five folds (from 0.46 to 1.95 IU ml⁻¹) respectively in 36 h. The production time decreased to 24 h compare to shake flask on Up-scaling the production process upto 10 L scale, thus increasing the productivity of cell bound (1810 IU DCG⁻¹day⁻¹) and extracellular phytase (6.08 IU ml⁻¹ day⁻¹). The crude phytase (12 IU) from NCIM 3321 strain was studied for plant growth promotion activity in lab scale and field level experiments with maize crop. Findings of the study revealed that the extracellular phytase derived from non pathogenic C. tropicalis (NCIM 3321) was found to be plant growth stimulating by increasing the available P in soil. Our findings of phytase isolated from non-pathogenic yeast C. tropicalis NCIM 3321 exhibited dephytinization potential. Therefore, current study may have profound application in sustainable agriculture.

Early detection of KP.2 SARS-CoV-2 variant using wastewater-based genomic surveillance in Pune, Maharashtra, India - Rajput, Vinay; Das, Rashmita; Pramanik, Rinka; Nannaware, Kiran; Sushma, Y.; Taji, Nyabom; Rajput, Vishal; Rajkhowa, Riyakshi; Pacharne, Poonam; Shah, Priyanki; Gogate, Niharika; Sangwar, Poornima; et al. (Journal of Travel Medicine, 2024)

Exploring the mechanisms of yoga-based cardiac rehabilitation in heart failure via assessment of endothelial function, genomics and arterial health (Yoga-EndOmics): a study protocol - Shetty, Vindya Vasu; Patil, Laxmi Ramchandra; Patil, Satish G.; Aithal, Kiran; Oli, Ajay Kumar; Yenagi, Vijay Aravind; Kaulgud, Ram S.; Dharne, Mahesh; Chandra Sekaran, Ambalam M.; Prabhakaran, Dorairaj (BMJ Open, 2026)
Introduction Heart failure (HF) remains a major global health challenge, particularly in low-resource settings where access to comprehensive cardiac rehabilitation (CR) is limited. Yoga, a culturally contextualised mind-body intervention, holds promise as an adjunctive therapy in CR. The Yoga-EndOmics study aims to evaluate the effects of Yoga-based cardiac rehabilitation (Yoga-CaRe) on gene expression, endothelial function, vascular biomarkers and clinical outcomes in systolic HF, providing mechanistic insights into its potential integration into conventional cardiac rehabilitation.Methods and analysis This is a prospective, randomised, open-label, blinded-endpoint (PROBE) mechanistic trial enrolling 78 patients with HF with reduced ejection fraction (HFrEF). Participants will be randomised in a 1:1 ratio to receive either a structured Yoga-CaRe intervention or enhanced standard care for 3 months. The Yoga-CaRe group will attend 20 supervised sessions with guided home practice involving tailored asanas, pranayama and meditation. Primary outcomes are changes in endothelial-dependent flow-mediated dilation (FMD) and functional exercise capacity at 3 months. Secondary outcomes include changes in arterial compliance and stiffness, circulating biomarkers of endothelial dysfunction, oxidative stress and inflammation, and immediate changes in global gene expression profiles in peripheral blood mononuclear cells following the Yoga-CaRe intervention. Data will be analysed using analysis of covariance (ANCOVA) for between-group comparisons and significant analysis of microarray (SAM) for global gene expression profiles.Ethics and dissemination The study has received ethical clearance from the Institutional Ethics Committee of the SDM College of Medical Sciences and Hospital, India (SDMIEC/2025/1072) and is registered with the Clinical Trials Registry of India. Findings will be disseminated through peer-reviewed journals, scientific conferences and stakeholder engagement platforms to inform future integrative strategies in HF management.Trial registration number CTRI/2023/12/060758
Keywords: DNA Methylation; Genetics; Heart failure; Molecular Biology; Randomized Controlled Trial